Karakteristik kerang bulu (Anadara antiquata) dan potensinya sebagai abon - Michael Ricky Sondak; Hari Minantyo; Ika Yohanna Patiwi; Ratu Padma Ap-Fatsah; Jason Lau (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Shellfish are known food sources that contain various important nutrients such as protein, fat and minerals. The purpose of this research is to establish the properties of Anadara antiquata and whether it may be used as a supplementary material for manufacturing abon. This study was divided into two stages: characterisation of fresh Anadara antiquata and preliminary examination of its absorption potential. This test uses Inductively Coupled Plasma Mass Spectrometry (ICP MS) which is a very reliable and versatile element detection method for determining levels of Cd, Pb, As and Hg. Potential abon using in this research combining Anadara antiquata with Chanos chanos and the other one using the addition of tempeh. Heavy metals analysis results show that all samples had an Cd content below 0.1 mg/kg, the weight Pb value was below 0.3 mg/kg, As value below 1,0 mg/kg and not detected Hg for all samples. All samples having a heavy metal content are below the threshold determined through SNI No 7690.1:2013. The addition of tempeh to the abon of Anadara antiquata can increase protein content with the highest number at 25.6%.